Lithium battery diaphragm and preparation method thereof
By adding nano microcapsules and ceramic materials to the coating of the lithium battery separator, a lithium battery separator with its own fire extinguishing function is solved, and the existing lithium battery separator cannot be extinguished when heat is out of control or fire is realized, the lithium battery is Improve safety and environmentally friendly fire extinguishing effects.
Patent Information
- Application Number
- CN202411477218.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-22
AI Technical Summary
The existing lithium battery separators cannot effectively extinguish the fire when there is thermal runaway or fire, which poses safety hazards.
Nano-microcapsules are used as fire extinguishing agents, and nano-microcapsules use perfluorohexanone as the core, polyurethane or polymethyl methacrylate as the shell. By adding nano-microcapsules and ceramic materials to the coating of lithium battery separators, a kind of self-contained self-contained Lithium battery diaphragm with fire extinguishing function.
When a lithium battery has thermal runaway or fire, the perfluorohexanone in the nano microcapsules expands heat, breaking through the microcapsule film, and automatically ejecting it, achieving the fire extinguishing effect through heat absorption and cooling, improving the safety of the lithium battery, and using Perfluorohexanone is a green and environmentally friendly fire extinguishing agent.
Smart Images

Figure CN119401063A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery separators, and in particular relates to a lithium battery separator and a preparation method thereof. Background Art
[0002] With the advancement of science and technology, lithium-ion batteries are widely used in various electronic devices due to their advantages such as high energy density and long cycle life. However, lithium-ion batteries also have safety hazards such as fire and explosion. In order to improve the safety of lithium batteries, the existing technology mainly coats a layer of ceramic material on the diaphragm to prevent internal short circuits in the battery. However, this method cannot effectively extinguish fires when thermal runaway occurs in the battery. Therefore, it is urgent to develop a lithium battery diaphragm with built-in fire extinguishing function. Summary of the invention
[0003] In view of the deficiencies in the prior art, an object of the present invention is to provide a slurry.
[0004] Another object of the present invention is to provide a method for preparing the slurry.
[0005] Another object of the present invention is to provide a lithium battery separator.
[0006] Another object of the present invention is to provide a method for preparing the above-mentioned lithium battery separator.
[0007] The purpose of the present invention is achieved through the following technical solutions.
[0008] A slurry comprises: nano-microcapsules, ceramics and water, wherein the ratio of the nano-microcapsules to the ceramics is (10-30):(70-90) by weight, the nano-microcapsules are capsules with perfluorohexanone as the core and a polymer as the shell, and the polymer is one or a mixture of polyurethane (PU) and polymethyl methacrylate (PMMA).
[0009] In the above technical solution, the slurry also includes: a binder and an additive, and the ratio of the mass fraction of the nanocapsules, the volume fraction of the binder and the volume fraction of the additive is (10-30): (2-3): (0.01-1), the unit of the mass fraction is mg, and the unit of the volume fraction is mL.
[0010] In the above technical solution, the particle size of the nano-microcapsules does not exceed the micron level.
[0011] In the above technical solution, the ceramic is one of alumina powder and titanium silicate powder.
[0012] In the above technical solution, the adhesive is one or a mixture of polyacrylate, acrylic resin and polyester resin.
[0013] In the above technical solution, the additive is one or more of a leveling agent, a defoaming agent and a pore-forming agent, the leveling agent is polydimethylsiloxane, the defoaming agent is polymethylsiloxane, and the pore-forming agent is isopropyl alcohol.
[0014] In the above technical solution, the ratio of ceramic to water is 1:(1.2-2.4) by mass.
[0015] When the slurry includes a binder and an additive, the method for preparing the slurry includes the following steps:
[0016] S1, mixing the nano-microcapsules and the ceramic coating until uniform to obtain a first solution, wherein the ceramic coating is a mixture of ceramic and water, and the ratio of the nano-microcapsules to the ceramic in the ceramic coating is (10-30): (70-90) by weight;
[0017] In S1, the nano-microcapsules and the ceramic coating are mixed and stirred at a rotation speed of 200 to 1500 rpm for 30 to 45 minutes until they are uniform.
[0018] In S1, the ratio of ceramic to water is 1:(1.2-2.4) by mass.
[0019] S2, mixing the first solution, the binder and the additive until uniform, to obtain the slurry, wherein the ratio of the mass fraction of the nano-microcapsules, the volume fraction of the binder and the volume fraction of the additive is (10-30): (2-3): (0.01-1), the unit of mass fraction is mg, and the unit of volume fraction is mL.
[0020] In the above technical solution, the method for preparing nano-microcapsules comprises the following steps:
[0021] Step 1, mixing perfluorohexanone, an emulsifier, a stabilizer and a polymer solution, emulsifying, and obtaining a first substance, wherein the ratio of perfluorohexanone, the emulsifier, the stabilizer and the polymer in the polymer solution is (10-15): (1-1.5): (0.5-1): (0.5-1.5) by weight;
[0022] In step 1, the polymer solution is a mixture of a polymer and a solvent, and the mass fraction of the polymer in the polymer solution is 0.5-0.7 wt%.
[0023] In step 1, the emulsifier is one or a mixture of Tween 60, Tween 80 and Pluronic F127.
[0024] In step 1, the stabilizer is one or a mixture of polyvinyl alcohol (PVA) and polyvinyl pyrrolidone (PVP).
[0025] In step 1, the polymer is one or a mixture of polyurethane (PU) and polymethyl methacrylate (PMMA).
[0026] In the above technical solution, the solvent is one or a mixture of N,N-dimethylformamide (DMF), dimethylacetamide (DMAc) and ethyl cellosolve.
[0027] In step 1, the emulsification temperature is 30-40° C. and the emulsification pressure is 1 atm.
[0028] Step 2, adding an initiator to the first substance to make the polymer undergo polymerization reaction again. After the polymerization reaction is completed, centrifugation, washing and drying are performed to obtain nano-microcapsules, wherein the ratio of perfluorohexanone to the initiator is (10-15): (0.1-0.2) by mass.
[0029] In step 2, the initiator is one or a mixture of potassium persulfate, ammonium persulfate and azobisisobutyronitrile.
[0030] In step 2, the centrifugal speed is 4000-4500 rpm, and the centrifugal time is 15-30 minutes.
[0031] In step 2, the washing adopts anhydrous ethanol or methanol. A lithium battery separator comprises: a base film and a coating coated on the base film, the coating comprises: nano-microcapsules and ceramics, the ratio of the nano-microcapsules to the ceramics is (10-30): (70-90) by weight, the nano-microcapsules are capsules with perfluorohexanone as the core and a polymer as the shell, the polymer is one of polyurethane (PU) and polymethyl methacrylate (PMMA) or a mixture of both, and the ceramic is one of alumina powder and titanium silicate powder.
[0032] The method for preparing the lithium battery diaphragm comprises: coating the slurry on one side or both sides of a base film, and drying the base film to obtain the lithium battery diaphragm.
[0033] In the above technical solution, the coating method is one of roller coating, spray coating and dip coating.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] The present invention realizes the self-contained fire extinguishing function of the lithium battery by adding nano-microcapsules to the coating of the lithium battery diaphragm. When the lithium battery has thermal runaway or fire, under the influence of external heat and flame, the perfluorohexanone in the nano-microcapsules will expand due to the heat, eventually break through the microcapsule film, and automatically spray out, achieving the effect of extinguishing the fire by absorbing heat and cooling. This method not only improves the safety of the lithium battery, but also the perfluorohexanone used is a green and environmentally friendly fire extinguishing agent, which is friendly to the environment. The present invention has broad application prospects and market value. On this basis, the synergistic effect of the nano-microcapsules and ceramics also improves the breakdown voltage of the diaphragm. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 Schematic diagram of the distribution of ceramics and nano-microcapsules in the coating of the present invention. DETAILED DESCRIPTION
[0037] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0038] The raw material information involved in the following examples is as follows:
[0039] Perfluorohexanone: Molecular formula: C 6 F 12 O.
[0040] Polymethyl methacrylate (PMMA): weight average molecular weight 300,000-600,000.
[0041] The polymer is polyurethane (PU): weight average molecular weight 150,000-400,000.
[0042] The instrument information involved in the following examples is as follows:
[0043] In the following embodiments, the base film is a PE film with a thickness of 9 um.
[0044] The particle sizes of the nano-microcapsules in the following examples do not exceed the micrometer level.
[0045] Example 1
[0046] A method for preparing a slurry comprises the following steps:
[0047] S1, mixing the nano-microcapsules and the ceramic coating, stirring at a rotation speed of 300 rpm for 30 minutes in a double planetary mixer until the nano-microcapsules are uniformly dispersed, to obtain a first solution, wherein the ratio of the nano-microcapsules to the ceramic in the ceramic coating is 10:90 by weight, the nano-microcapsules are capsules with perfluorohexanone as the core and a polymer as the shell, the ceramic coating is a mixture of ceramic and water, the ceramic is aluminum oxide powder, and the ratio of the ceramic to water is 1:2 by weight;
[0048] S2, mixing the first solution, the adhesive and the additive until uniform to obtain a slurry, wherein the ratio of the mass fraction of the nanocapsules, the volume fraction of the adhesive and the volume fraction of the additive is 10:2:0.01, the unit of the mass fraction is mg, the unit of the volume fraction is mL, the adhesive is polymethyl acrylate, the additive is a leveling agent, and the leveling agent is polydimethylsiloxane. The adhesive and the leveling agent are added to improve the adhesion and surface smoothness of the coating.
[0049] The method for preparing nano-microcapsules comprises the following steps:
[0050] Step 1, mixing perfluorohexanone, an emulsifier, a stabilizer and a polymer solution, stirring at a speed of 15000 rpm for 15 minutes (emulsification) using a high-speed homogenizer at 40° C. and 1 atm, to obtain a first substance (stable oil-water emulsion), wherein the ratio of perfluorohexanone, the emulsifier, the stabilizer and the polymer in the polymer solution is 10:1:0.5:0.7 by mass, the polymer solution is a mixture of a polymer and a solvent, the mass fraction of the polymer in the polymer solution is 0.5wt%, the emulsifier is Tween 80, the stabilizer is polyvinyl alcohol (PVA), the polymer is polyurethane (PU), and the solvent is N,N-dimethylformamide (DMF);
[0051] Step 2, adding an initiator to the first substance (initiating the polymer to undergo polymerization reaction), stirring at 15000 rpm at 60°C for 180 min, after the polymerization reaction is completed, centrifuging at 4000 rpm for 30 minutes, washing with anhydrous ethanol for 3 times, and drying at 40°C for 24 hours to obtain nano-microcapsules, wherein the ratio of perfluorohexanone to initiator is 10:0.1 by mass, and the initiator is potassium persulfate.
[0052] Example 2
[0053] A method for preparing a slurry comprises the following steps:
[0054] S1, mixing the nano-microcapsules and the ceramic coating, stirring at a speed of 200 rpm in a double planetary mixer for 45 minutes until the nano-microcapsules are uniformly dispersed, to obtain a first solution, wherein the ratio of the nano-microcapsules to the ceramic in the ceramic coating is 20:80 by weight, the nano-microcapsules are capsules with perfluorohexanone as the core and a polymer as the shell, the ceramic coating is a mixture of ceramic and water, the ceramic is titanium silicate powder, and the ratio of the ceramic to water is 1:2 by weight;
[0055] S2, mixing the first solution, the adhesive and the additive until uniform to obtain a slurry, wherein the ratio of the mass fraction of the nanocapsules, the volume fraction of the adhesive and the volume fraction of the additive is 20:3:1, the unit of the mass fraction is mg, the unit of the volume fraction is mL, the adhesive is an acrylic resin, the additive is a defoamer, the defoamer is polymethylsiloxane, and the adhesive and the defoamer are used to improve the adhesion of the coating and reduce bubbles during the coating process.
[0056] The method for preparing nano-microcapsules comprises the following steps:
[0057] Step 1, mixing perfluorohexanone, an emulsifier, a stabilizer and a polymer solution, stirring at a speed of 12000 rpm for 20 minutes using a high shear mixer at 30°C and 1 atm (emulsification), to obtain a first substance (a stable oil-water mixture), wherein the ratio of perfluorohexanone, the emulsifier, the stabilizer and the polymer in the polymer solution is 15:1.5:1.0:1.0 by weight, the polymer solution is a mixture of a polymer and a solvent, the mass fraction of the polymer in the polymer solution is 0.7wt%, the emulsifier is Pluronic F127, the stabilizer is polyvinyl alcohol (PVA), the polymer is polymethyl methacrylate (PMMA), and the solvent is dimethylacetamide (DMAc);
[0058] Step 2, adding an initiator to the first substance (initiating the polymer to undergo polymerization reaction), stirring at a speed of 12000 rpm at 30°C for 60 minutes, after the polymerization reaction is completed, centrifuging at 4500 rpm for 20 minutes, washing with anhydrous ethanol for 4 times, and drying at 45°C for 18 hours to obtain nano-microcapsules, wherein the ratio of perfluorohexanone to initiator is 15:0.2 by mass, and the initiator is ammonium persulfate.
[0059] Example 3
[0060] A method for preparing a slurry comprises the following steps:
[0061] S1, mixing the nano-microcapsules and the ceramic coating, stirring in a double planetary mixer at a speed of 1500 rpm for 30 minutes until the nano-microcapsules are uniformly dispersed, to obtain a first solution, wherein the ratio of the nano-microcapsules to the ceramic in the ceramic coating is 30:70 by weight, the nano-microcapsules are capsules with perfluorohexanone as the core and a polymer as the shell, the ceramic coating is a mixture of ceramic and water, the ceramic is aluminum oxide powder, and the ratio of the ceramic to water is 1:2 by weight;
[0062] S2, mixing the first solution, the adhesive and the additive until uniform to obtain a slurry, wherein the ratio of the mass fraction of the nanocapsules, the volume fraction of the adhesive and the volume fraction of the additive is 30:2:0.5, the unit of the mass fraction is mg, the unit of the volume fraction is mL, the adhesive is a polyester resin, the additive is a pore-forming agent, and the pore-forming agent is isopropyl alcohol. The adhesive and the pore-forming agent are added to improve the mechanical properties of the coating.
[0063] The method for preparing nano-microcapsules comprises the following steps:
[0064] Step 1, mixing perfluorohexanone, an emulsifier, a stabilizer and a polymer solution, and using an ultrasonic emulsifier to ultrasonicate for 15 minutes at 1kHz under the conditions of 40°C and 1atm (emulsification) to obtain a first substance (stable emulsion), wherein the ratio of perfluorohexanone, the emulsifier, the stabilizer and the polymer in the polymer solution is 13:1.2:0.8:0.8 by mass, the polymer solution is a mixture of a polymer and a solvent, the mass fraction of the polymer in the polymer solution is 0.6wt%, the emulsifier is Tween60, the stabilizer is polyvinyl pyrrolidone (PVP), the polymer is polymethyl methacrylate (PMMA), and the solvent is dimethylacetamide (DMAc);
[0065] Step 2, adding an initiator to the first substance (initiating the polymer to undergo polymerization reaction), stirring at 40°C for 45 minutes at a speed of 500 rpm. After the polymerization reaction is completed, centrifuging at 4000 rpm for 15 minutes, washing with methanol 3 times, and drying at 40°C for 24 hours to obtain nano-microcapsules, wherein the ratio of perfluorohexanone to initiator is 13:0.15 by mass, and the initiator is azobisisobutyronitrile.
[0066] Comparative Example 1
[0067] A method for preparing a lithium battery diaphragm comprises: transferring a conventional alumina slurry to a coating tank of a coating machine, adjusting the liquid level to ensure continuous coating, coating the conventional alumina slurry on a single side of a base film by lithographic coating (the coating speed is set to 60 m / min), drying in a hot air drying oven at 50° C. for 5 minutes, obtaining a coating on the base film (the coating thickness is 3 μm, and the coating thickness is controlled by adjusting the coating gap), and obtaining a lithium battery diaphragm, wherein the method for obtaining the conventional alumina slurry is: dispersing alumina powder in deionized water, grinding with a sand mill until the D50 particle size reaches 0.9 μm to ensure good dispersibility, obtaining an alumina dispersion, adding a dispersant (sodium polyacrylate) to the alumina dispersion to prevent particle aggregation, and ultrasonically treating until uniform dispersion, to obtain a conventional alumina slurry, wherein the ratio of alumina powder, deionized water and dispersant is 30:50:2 by mass.
[0068] Embodiments 4 to 6
[0069] A method for preparing a lithium battery separator comprises: transferring a slurry to a material tank of a coating machine, adjusting the liquid level of the material tank to ensure a stable supply of the slurry during coating, coating the slurry on a single side of a base film using a micro-gravure coating roller, drying at A°C for 1 min, obtaining a coating on the base film (the coating thickness is 3 um, and the coating thickness is controlled by adjusting the coating gap), and obtaining a lithium battery separator, wherein the line number of the micro-gravure coating roller is 120 lines / inch (the line number is used to ensure uniform coating), the coating speed is B m / min, and the slurry is one of the slurries prepared in Examples 1 to 3. The values of A and B are shown in Table 1.
[0070] Table 1
[0071]
[0072] The performance tests of the lithium battery separators prepared in Examples 4 to 6 and Comparative Example 1 were performed, and the results are shown in Table 2, wherein the "fire extinguishing effect" was obtained through a fire extinguishing experiment. The fire extinguishing experiment was as follows: a base film with a length of 10 cm and a width of 1 cm was cut, and the slurry was applied to the first 5 cm to obtain a coating film. Ignite at one end of the base film not coated with the slurry, start timing at the place where the flame burns to the boundary between the base film and the coating film, and record the time when the flame is extinguished. The time when the flame is extinguished is shown in Table 2. The shorter the time, the better the fire extinguishing effect.
[0073] Table 2
[0074]
[0075] Experimental conclusion: With the increase of nano-microcapsule content, the breakdown voltage resistance of lithium battery diaphragm becomes better and better, and the fire extinguishing effect becomes better and better.
[0076] like Figure 1 As shown in the figure, the distribution of nanocapsules is below the ceramic coating. The multiple interfaces of different materials improve the overall breakdown voltage of the diaphragm. Figure 1 Here, "ceramic" refers to alumina powder in the slurries of Examples 1 and 3, and refers to titanium silicate powder in the slurry of Example 2).
[0077] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A slurry, characterized in that: include: Nanocapsules, ceramics and water, in which the ratio of the nanocapsules to the ceramics is (10-30):(70-90) by weight. The nanocapsules are capsules with perfluorohexanone as the core and a polymer as the shell, and the polymer is one or a mixture of polyurethane and polymethyl methacrylate.
2. The slurry according to claim 1, characterized in that The slurry also includes: a binder and an additive, and the ratio of the mass fraction of the nano-microcapsules, the volume fraction of the binder and the volume fraction of the additive is (10-30): (2-3): (0.01-1), the unit of the mass fraction is mg, and the unit of the volume fraction is mL.
3. The slurry according to claim 2, characterized in that The ceramic is one of alumina powder and titanium silicate powder; the adhesive is one of polyacrylate, acrylic resin and polyester resin or a mixture of several of them; the additive is one of a leveling agent, a defoaming agent and a pore-forming agent.
4. The slurry according to claim 3, characterized in that The leveling agent is polydimethylsiloxane, the defoaming agent is polymethylsiloxane, and the pore-forming agent is isopropyl alcohol.
5. The slurry according to claim 1, characterized in that Calculated by mass, the ratio of ceramic to water is 1:(1.2~2.4).
6. The slurry according to claim 1, characterized in that The method for preparing nano-microcapsules comprises the following steps: Step 1, mixing perfluorohexanone, an emulsifier, a stabilizer and a polymer solution, emulsifying, and obtaining a first substance, wherein the ratio of perfluorohexanone, the emulsifier, the stabilizer and the polymer in the polymer solution is (10-15): (1-1.5): (0.5-1): (0.5-1.5) by weight; Step 2, adding an initiator to the first substance for polymerization reaction, and after the polymerization reaction is completed, centrifuging, washing, and drying to obtain nano-microcapsules, wherein the ratio of perfluorohexanone to the initiator is (10-15): (0.1-0.2) by mass.
7. The slurry according to claim 6, characterized in that In step 1, the emulsification temperature is 30-40° C. and the emulsification pressure is 1 atm.
8. The method for preparing the slurry according to claim 2, comprising the following steps: S1, mixing the nano-microcapsules and the ceramic coating until uniform to obtain a first solution, wherein the ceramic coating is a mixture of ceramic and water, and the ratio of the nano-microcapsules to the ceramic in the ceramic coating is (10-30): (70-90) by weight; S2, mixing the first solution, the binder and the additive until uniform, to obtain the slurry, wherein the ratio of the mass fraction of the nano-microcapsules, the volume fraction of the binder and the volume fraction of the additive is (10-30): (2-3): (0.01-1), the unit of mass fraction is mg, and the unit of volume fraction is mL.
9. A lithium battery separator, characterized in that: include: A base film and a coating coated on the base film, the coating comprising: nano-microcapsules and ceramics, wherein the ratio of the nano-microcapsules to the ceramics is (10-30):(70-90) by mass, the nano-microcapsules are capsules with perfluorohexanone as the core and a polymer as the shell, the polymer is one of polyurethane and polymethyl methacrylate or a mixture of both, and the ceramic is one of alumina powder and titanium silicate powder.
10. The application of nano-microcapsules and ceramics to synergistically improve the safety of lithium batteries and the breakdown voltage of diaphragms.
Citation Information
Patent Citations
Diaphragm slurry capable of efficiently capturing metal ions, diaphragm and application of diaphragm
CN111081953A
Fire extinguishing diaphragm capable of actively inhibiting thermal runaway of lithium battery as well as preparation method and application of fire extinguishing diaphragm
CN113193301A
Lithium ion battery capable of blocking thermal runaway stage by stage and preparation method of lithium ion battery
CN115939516A
Cited By
Diaphragm, secondary battery and electric device
CN120914452A